2011
DOI: 10.14310/horm.2002.1290
|View full text |Cite
|
Sign up to set email alerts
|

Molecular parameters linking thyroglobulin iodination with autoimmune thyroiditis

Abstract: Increased iodide intake has been linked to the development of hypothyroidism and/or autoimmune thyroiditis in humans and animals, but the mechanisms involved remain poorly understood. Increased ingestion of iodide is likely to have pleiotropic effects on either metabolic or immunological processes. Within the latter domain, recent interest has been focused on two areas: a) the role of iodinated peptides in thyroglobulin (tg)-the molecular site of biosynthesis and storage of iodotyrosines and iodothyronines-in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…The authors found a rising incidence of hypothyroidism (elevated serum thyrotropin), which was accompanied by the appearance/increase in thyroperoxidase antibodies (39). Nevertheless, despite epidemiological studies and animal experiments clearly indicating that more dietary iodine increases the incidence of autoimmune thyroiditis (40,41), the mechanism for the proimmunogenic effect of iodine remains to be explained (42).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a rising incidence of hypothyroidism (elevated serum thyrotropin), which was accompanied by the appearance/increase in thyroperoxidase antibodies (39). Nevertheless, despite epidemiological studies and animal experiments clearly indicating that more dietary iodine increases the incidence of autoimmune thyroiditis (40,41), the mechanism for the proimmunogenic effect of iodine remains to be explained (42).…”
Section: Discussionmentioning
confidence: 99%
“…Due to widespread use of iodized salt, hypothyroidism due to iodine deficiency is rare in North America. However, increased iodine intake has been linked to the development of autoimmune thyroiditis leading to hypothyroidism (Carayanniotis, 2011). We are not aware of the high prevalence of any such risk factors in the west and south coast communities.…”
Section: Discussionmentioning
confidence: 92%
“…Iodinated peptides in Tg as well as iodine-induced apoptosis/necrosis of thyrocytes trigger autoimmune thyroid disease [25]. Increased release of Tg temporarily increases anti-Tg level, and has been reported after thyroid surgery [26], RAI administration [27], and ethanol administration in toxic adenomas [28,29]. In our cases, during the acute phase of SAT, serum Tg levels were increased, whereas anti-Tg was normal, which was followed by development of increased anti-Tg levels 3 months later, with the appearance of GD.…”
Section: Discussionmentioning
confidence: 99%